¿Como una caña en el cañaveral? - Dante Barrientos Tecún; Marie-Christine Seguin (Caravelle)
This paper introduces a sample of Central American literary production and a sample of spanish speaking Caribbean Islands’ poets refering to Sugar cane. A Central American production which seems less abundant than that of the Caribbean zone in spite of the fact that it begins in the 18th century with the Jesuit poet Rafael Landívar. In the 20th century, sugar cane including its labor and derived products, is represented in the texts of the “criollistas” narrators and poets. Paradoxically, while the sugar production becomes more important for agro-exportation, it “disappears” from literature which takes hold of different urban themes or those related to the political violence instead. However, in the most recent productions of Caribbean poems, an innovation appears in the treatment of this topic that, from the traditions, adapts itself to modern forms of transmission.